Branch Migration Prevents DNA Loss during Double-Strand Break Repair - Mawer, Julia S. P. (Public Library of Science, 2014)
The repair of DNA double-strand breaks must be accurate to avoid genomic rearrangements that can lead to cell death and disease. This can be accomplished by promoting homologous recombination between correctly aligned sister chromosomes. Here, using a unique system for generating a site-specific DNA double-strand break in one copy of two replicating Escherichia coli sister chromosomes, we analyse the intermediates of sister-sister double-strand break repair. Using two-dimensional agarose gel electrophoresis, we show that when double-strand breaks are formed in the absence of RuvAB, 4-way DNA (Holliday) junctions are accumulated in a RecG-dependent manner, arguing against the long-standing view that the redundancy of RuvAB and RecG is in the resolution of Holliday junctions. Using pulsed-field gel electrophoresis, we explain the redundancy by showing that branch migration catalysed by RuvAB and RecG is required for stabilising the intermediates of repair as, when branch migration cannot take place, repair is aborted and DNA is lost at the break locus. We demonstrate that in the repair of correctly aligned sister chromosomes, an unstable early intermediate is stabilised by branch migration. This reliance on branch migration may have evolved to help promote recombination between correctly aligned sister chromosomes to prevent genomic rearrangements.